Pengaruh Kualitas Produk Dan Promosi Melalui Media Sosial Instagram Terhadap Keputusan Pembelian Di Hans Street Cafe - Yesaya Stevan Munthe; Agus Rahmadsyah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to determine the influence of product quality on purchase decisions and to determine the influence of promotion through Instagram social media on purchase decisions at Hans Street Cafe. The sampling technique used was the purposive sampling technique, the sample used was 96 respondents of Hans Street Cafe consumers while the analysis tools used were multiple linear regression analysis, classical assumption test, t test, f test and determination coefficient (R2). Based on the results of the study, it is known that the Product Quality variable (X1) has a positive and significant influence on Purchase Decisions (Y) of 0.420 and significance of 0.000. Promotion Through Instagram Social Media (X2) also has a positive and significant influence on Purchase Decisions (Y) of 0.540 and significance of 0.000. Simultaneously, the two variables, namely Product Quality (X1) and Promotion Through Instagram Social Media (X2), have a positive and significant influence on Purchase Decisions at Hans Street Cafe.